PRELIMINARY REVISIONS OF SOME GENERA OF MALAYSIAN PAPILIONACEAE IV - A REVISION OF ORMOSIA - m. s. knaap; van meeuwen (REINWARDTIA, 1962)
In this revision 11 species have been admitted for the Malaysian Archipelago, including 0. stipidacea which is described as new, from Brunei. A key, synonymy, and distribution are given. Ten species and one variety are reduced; three of these reductions (under O. macrodisea) are tentative, as of two of them no types were available. Another species, 0. villamilii Merr., is reduced to Pericopsis moonii. O. scandens, of which I ' have also seen no material, I have not been able to place; its pod is unknown.